Le fratture del capitello radiale in età infantile - De Pellegrin, M.; Marcucci, L.; Rosenlechner, T.; Fracassetti, D. (Lo Scalpello - Journal, 2018)
RADIAL NECK FRACTURES IN CHILDREN Fractures of the radial neck are rare and account for approximately one percent of all bone fractures in childhood, while severe displaced fractures account for only 1/3 of those. According to the literature, the main complications of surgical treatment include loss of function and avascular necrosis. The aim of the study was to describe our mini-invasive technique and to compare it to eighteen minimally-invasive techniques found after a literature review. Between 1990 and 2017 twelve patients (7 males and 5 females) aged between one and thirteen years (average age 8.3 years) with severe displaced radial neck fractures (6 type III, 4 type IVa and 2 type IVb according to Judet’s classification) were treated with a minimally-invasive technique combining percutaneous Kirschner wire reduction and intramedullary fixation according to Métaizeau. The Metaizeau radiological and functional score evaluation and the functional score of Tibone and Stoltz were considered. The postoperative x-ray evaluation according to Metaizeau showed eleven excellent results and one good result. After an average follow-up of 28 months (range 8–110 months) the scores according to Tibone and Stoltz showed 10 excellent results and two good results; the functional evaluation according to Métaizeau showed 11 excellent results and one good result. Percutaneous reduction of the displaced radial head in radial neck fracture using a Kirschner wire combined with an intramedullary fixation according to Metaizeau has proven to be simple, effective and without complications.